Evolution des rôles du psychologue scolaire - Gauthier, Gaston (Canadian Journal of Counselling and Psychotherapy, 2012)
The school psychologist is answering the pupils' needs through individual centered interventions and psychological learning processes. School expectations are not satisfied by the clinical and psycho-educational approaches. An eco-systemic approach would be an efficient complement to the traditional types of intervention.